Perspektif ECM Tentang Perangkap Pendapatan Menengah di Indonesia Tantangan dan Strategi - Syam, Fauziyah; Amaliah, Ima (Jurnal Riset Ilmu Ekonomi, 2024)
This research aims to identify and analyze the factors that cause Indonesia to fall into the middle-income trap category, as indicated by the manufacturing sector, education level and number of MSMEs. This research uses quantitative with error corection model methods. The data used is from 1997-2022. The data used consists of manufacturing value added, school enrollment rates, number of MSMEs and per capita income used as a middle-income trap proxy sourced from the World Bank, BPS and ukmindonesia.id. The results of data processing show that the manufacturing industry has a negative effect on the middle-income trap in both the long and short term. The direction of the variable relationship is in accordance with theory. An increase in manufacturing industry will reduce MIT. However, the level of education and the number of MSMEs have a positive influence on MIT because most of Indonesia's APS is dominated by a reasonable salary of 9-12 years and MSMEs are only able to absorb small-scale workers. Indonesia is expected to be expelled from MIT within 6 years or 2030.